Solar-assisted steam power plant retrofitted with regenerative system using Parabolic Trough Solar Collectors - Sorour Alotaibi; Fahad Alotaibi; Osama M. Ibrahim (Energy Reports, 2020)
This work investigates the performance of a conventional steam power plant retrofitted with a solar-assisted regenerative system using Parabolic Trough Solar Collectors (PTC). The solar collectors were used to compensate for the effect of removing Low-Pressure (LP) turbine extractions without changing other elements of a 300 MW power plant unit during peak load operations. The steam power plant, located in Kuwait, receives high levels of solar irradiation. Modeling of the solar-assisted regenerative system using PTC is simulated for Kuwait's weather conditions. Results of the system analysis show that removing the LP turbine extractions enhanced the performance of the steam power plant by 9.8 MW, with an optimum PTC aperture area equal to 25,850 m2. A techno-economic analysis was used to estimate the Levelized Cost of Energy (LCOE). Compared to an equivalent photovoltaic solar plant, the optimum aperture area and LCOE for the PTC solar plant were found to be less by 45% and 44%, respectively. When compared to an equivalent conventional steam turbine, the solar-assisted steam power plant decreased cost by 56% over the lifecycle of 25-years.
Keywords: 330; Steam power plants; Solar-assisted; Regenerative system